Co-diversification of Enterococcus faecium Core Genomes and PBP5: Evidences of pbp5 Horizontal Transfer - Novais, Carla; Tedim, Ana P.; Lanza, Val F.; Freitas, Ana R.; Silveira, Eduarda; Escada, Ricardo; Roberts, Adam P.; Al-Haroni, Mohammed; Baquero, Fernando; Peixe, Luísa; Coque, Teresa M. (Frontiers in Microbiology, 2016)
Ampicillin resistance has greatly contributed to the recent dramatic increase of a cluster of human adapted Enterococcus faecium lineages (ST17, ST18, and ST78) in hospital-based infections. Changes in the chromosomal pbp5 gene have been associated with different levels of ampicillin susceptibility, leading to protein variants (designated as PBP5 C-types to keep the nomenclature used in previous works) with diverse degrees of reduction in penicillin affinity. Our goal was to use a comparative genomics approach to evaluate the relationship between the diversity of PBP5 among E. faecium isolates of different phylogenomic groups as well as to assess the pbp5 transferability among isolates of disparate clonal lineages. The analyses of 78 selected E. faecium strains as well as published E. faecium genomes, suggested that the diversity of pbp5 mirrors the phylogenomic diversification of E. faecium. The presence of identical PBP5 C-types as well as similar pbp5 genetic environments in different E. faecium lineages and clones from quite different geographical and environmental origin was also documented and would indicate their horizontal gene transfer among E. faecium populations. This was supported by experimental assays showing transfer of large (≈180–280 kb) chromosomal genetic platforms containing pbp5 alleles, ponA (transglycosilase) and other metabolic and adaptive features, from E. faecium donor isolates to suitable E. faecium recipient strains. Mutation profile analysis of PBP5 from available genomes and strains from this study suggests that the spread of PBP5 C-types might have occurred even in the absence of a significant ampicillin resistance phenotype. In summary, genetic platforms containing pbp5 sequences were stably maintained in particular E. faecium lineages, but were also able to be transferred among E. faecium clones of different origins, emphasizing the growing risk of further spread of ampicillin resistance in this nosocomial pathogen.